Nitric Oxide Crosstalk With Phytohormone Is Involved in Enhancing Photosynthesis of Tetrastigma hemsleyanum for Photovoltaic Adaptation - Xie, Zhuomi; Yang, Chuyun; Li, Mingjie; Zhang, Zhongyi; Wu, Yao; Gu, Li; Peng, Xin (Frontiers in Plant Science, 2022)
Photovoltaic agriculture is a newly emerging ecological planting pattern. In view of the adverse effect on production, a better understanding of photovoltaic adaptation responses is essential for the development of the innovative agriculture mode in sustainable crop production. Here, we investigated the impact of photovoltaic condition on endogenous hormone composition and transcriptome profile of T. hemsleyanum. A total of 16 differentially accumulated phytohormones and 12,615 differentially expressed genes (DEGs) were identified. Photovoltaic adaptation significantly decreased the contents of phytohormones especially SA and JA. DEGs were the most relevant to photosynthesis and MAPK signaling pathway. A total of 16 key genes encoding proteins involved in photosystem I (PS I) and photosystem II (PS II) reaction center was down-regulated. NO, JA, and SA treatment alone significantly enhanced photosynthetic efficiency which was decreased by exposure to photovoltaic condition, but the combined treatment of “NO + SA” could weaken the enhancement effect. An antagonistic link between SA and NO was also found in promoting the expression level of psaL, CHIL, petF1, psbQ, and psaE genes. Exogenous phytohormones and NO treatment mitigated the accumulation of ROS and potentiated antioxidant capacity, but the combined treatment of “NO + SA” could weaken the roles. SA and JA significantly decreased endogenous NO burst triggered by photovoltaic adaptation. SA might also be a potent scavenger of NO and counter the restoration effect of NO on growth and photosynthetic potential in T. hemsleyanum. The results would lay the foundation for the application of phytohormones/ other signaling molecules in photovoltaic agriculture.